Interracial communication : theory into practice - Orbe, Mark P.; Harris, Tina M. (London : SAGE Publications, Ltd, 2015)
This Third Edition of Interracial Communication: Theory Into Practice guides readers in applying the contributions of recent communication theory to improving everyday communication among the races. Authors Mark P. Orbe and Tina M. Harris offer a comprehensive, practical foundation for dialogue on interracial communication, as well as a resource that stimulates thinking and encourages readers to become active participants in dialogue across racial barriers. Part I provides a foundation for studying interracial communication and includes chapters on the history of race and racial categories, the importance of language, the development of racial and cultural identities, and current and classical theoretical approaches. Part II applies this information to interracial communication practices in specific, everyday contexts, including friendships, romantic relationships, the mass media, and organizational, public, and group settings. This Third Edition includes the latest data, new research studies and examples, all-new photos, and important new topics.
Includes bibliographical references and index.
Description based on XML content.
Keywords: Cultural pluralism -- United States; Intercultural communication -- United States; United States -- Race relations; United States -- Ethnic relations